MODEL DAN STRATEGI PENGEMBANGAN KAWASAN EKOWISATA HUTA MANGROVE DI DESA BAHOI KECAMATAN LIKUPANG - Lagarense, Bet El; Ruslani; Tarlemba, Mardila (Jurnal Ilmu Pariwisata, 2023)
Ecotourism is a sustainable tourism development concept that aims to support environmental conservation efforts and increase community participation. The current management system for ecotourism activities in Bahoi village is not optimal. Collection of fees and marketing of ecotourism products to the wider community has not gone well. Several facilities supporting ecotourism activities have begun to be damaged and destruction of mangroves by the community around Bahoi village is still occurring to this day and ecotourism activities currently only focus on marine tourism. The development of mangrove forest ecotourism areas provides economic benefits for local communities, but its management requires cooperation between the community and the government. Arranging ecotourism areas, adding and improving infrastructure supporting ecotourism activities, and marketing systems and management systems for mangrove forest ecotourism areas are the main objectives of researchers in this research. The research was carried out in August-December 2018, data collection methods were carried out by direct observation in the field (observation), interviews, documentation and literature study. Data analysis was carried out using qualitative methods. Namely determining the model and strategy for developing the mangrove forest ecotourism area in Bahoi village. Based on the results of the research conducted, it can be concluded that there is a need for good management planning in developing mangrove forest ecotourism areas in order to improve the local community's economy. In addition, people's concern for the environment will increase.